Hospital infections in an emergency unit and an intensive care unit: similarities and differences - Adriana Cristina Oliveira; Adriana Oliveira Paula; Ana Clara Souza Lacerda; Fernanda Santiago Andrade; Robert Aldo Iquiapaza (Universidade Federal de Goias, 2014)
The objective of this study was to identify the similarities and differences between the emergency unit and the intensive care unit regarding patients' risk to develop infections and its associated factors. This cross-sectional study was performed with data collected by active surveillance between August/2009 and October/2010. Descriptive statistics, t and Chi-squared tests, logistic regression and 5% significance were used. A total 1,157 patients were included, 334 of which were from the emergency unit and 823 from the intensive care unit. The infection sites were similar, but the resistance profile of causal agents, as well as risk factors and death were different. The mortality rate was similar, indicating the severity of the patients in both settings. Despite the fact that the emergency unit did not function exactly like the intensive care unit, both have become significant settings in the dissemination of infections and microorganisms, and determine a high mortality rate. Descriptors: Intensive Care Units; Emergency Service, Hospital; Cross Infection; Risk Factors; Nursing.